The Effect Of The Internal Control System On The Quality Of Financial Reports At Pt Perkebunan Nusantara XIV Makassar - Haerunnisa, Haerunnisa; Linda Arisanty Razak; Muchriana Muchran (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine the effect of the internal control system on the quality of financial reports at PT Perkebunan Nusantara XIV Makassar. This research was conducted to get an overview regarding whether the internal control system is able to influence the quality of financial reports at PT Perkebunan Nusantara XIV Makassar. This type of research is a case study. This research was conducted at PT Perkebunan Nusantara XIV Makassar. The type of data used is quantitative and qualitative data while the data sources are primary and secondary. Methods of data collection using documentation techniques and questionnaires. The data analysis technique uses simple linear regression with SPSS version 25 assisted testing. The results of the study indicate that the independent variable of the internal control system influences the dependent variable on the quality of financial reports. This can be seen from the magnitude of the influence of the internal control system on the quality of financial reports, which is equal to 20.5%